The Prosperity Level of Plasma Palm Oil Farmer’s Family in the State Border Area during the New Normal Era - Dahliani, Lili; Nurdialy, Mela; Relawati, Rahayu; Abduh, Muhamad (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
This study aimed to investigate and analyze: the demographic characteristics, prosperity levels, and factors affecting the prosperity level among the plasma palm oil farmers during the new normal era. This study was conducted in a palm oil plantation area, Kembayan, Sanggau Regency, West Borneo from August to July 2020. Primary data were collected using a questionnaire that directly distributed to the partisipants. The level of prosperity was measured by the prosperous family indicators from the National Population Planning and Family Board and poverty line indicators from the National Statistical Institute. A descriptive quantitative, descriptive qualitative, and multinomial logit regression analysis applied to address the study’s objectives. Findings revealed that 51%, 23%, 17%, 8%, and 1% of the farmer’s family were classified into the prosperous family level III plus, prosperous family level III, prosperous family level II, prosperous family level I, and pre-prosperous family category, respectively. According to poverty line indicators, all farmer’s state of living were placed above the line of poverty. These findings signified that palm oil businesses in the state border area were providing sufficient amount of revenue for the farmers during the new normal era. The variabel of age, total plantation land area, and income were associated with the farmer’s family prosperity level.